Improving Employee Performance Through Emotional Intelligence and Transformational Leadership: The Mediating Role of Work Engagement - Titik Sulistiana; Tjahjani Prawitowati (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of Emotional Intelligence (EI) and Transformational Leadership (TL) on Job Performance (JP), with Work Engagement (WE) as a mediating variable. The research object is employees in Karang Pilang District, Surabaya, using a quantitative explanatory approach through a closed-ended questionnaire survey. A sample of 100 respondents was obtained using the snowball sampling technique. EI was measured through self-awareness, self-management, social awareness, and relationship management. TL included idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. WE consisted of vigor, dedication, and full absorption. JP was measured based on task achievement, productivity, and responsibility. Data analysis was conducted using SEM-PLS with SmartPLS. The results of this study indicate that employee performance in Karang Pilang District, Surabaya, is influenced by emotional intelligence, transformational leadership, and work engagement. However, for transformational leadership not to have a negative impact on performance, a balance between innovation and stability as well as a participatory approach is required. This study is expected to provide both theoretical and practical contributions to improving employee performance in the public sector.